Differences in the city and village in terms of power consumption(case study: poldokhtar city) - Alireza Rahimi; Nader Nazemi; jamaleddin honarvar (تحقیقات کاربردی علوم جغرافیایی)
Energy plays a major role in providing welfare of urban and rural households, and reforming energy consumption patterns, in addition to price balancing, requires recognition and acts of cultural and social variables affecting the pattern of consumption and savings. Considering the importance of saving electricity and its relation with consumer behavior, in this study, the difference in urban and rural communities was investigated in terms of effective factors on energy savings. The present research is descriptive-analytical in terms of purpose and method. The data-gathering tool and information collection and interviews with urban and rural households in Poledokhtar city. The statistical population includes urban and rural households in Poledokhtar Township (N= 30012). Using Cochran formula and simple random sampling method, 379 households (244 urban households and 135 rural households) were selected. In the data analysis section, analysis of variance and logistic regression tests were used. The results showed that there is a significant difference between the factors and indicators affecting power saving in rural and urban areas. The individual agent and the factor of behavior management and purchasing, while the factor is the most important factor in saving households in rural areas, primarily influence power saving in urban areas.